PENGEMBANGAN MODEL PEMBELAJARAN KOPERATIF UNTUK PERKULIAHAN METODE PEKERJAAN SOSIAL - Dwi Heru Sukoco, - (2002)
The title of this dissertation is "Cooperative Learning Model Development for Teaching Social Work Methods." The goal is to develop a cooperative learning model that can improve the teaching quality of social work methods. The success of teaching is determined by the mastery of social work knowledge and teaching-learning methodology by the lecturers. The empirical conditions indicate that the mastery of learning model by the lecturers is inadequate, so that they are not able to develop interpersonal interaction, develop subject matter operationally, make students learn, develop attractive learning conditions, enhance learning motivation, and conduct objective and fast learning evaluation. Cooperative learning is a learning model using a heterogenous small team to improve the ability of the students to master the teaching materials, and to enhance the social skills, problem solving ability, self-confidence, and self-esteem. The development of the cooperative learning model in teaching social work methods is aimed at enhancing the quality, so that it can contribute to the achievement of one of the goals of the national education, that is the improvement of educational quality. The underlying theories are theories of social work, group learning, and cooperative learning. The method of the study used is research and development, that includes: presurvey, preparation of the model draft, testing of the model, and testing of validation of the model. The unit of analyses are the social work lecturers and students at the Bandung School of Social Welfare, Padjadjaran University, and Pasundan University. The data collection techniques used are interview, questionnaire, observation, and testing. The data analyses used are descriptive statistics, t-test, and analysis of variance. The results of the study indicate that the application of the cooperative learning model can improve the performance of the lecturers, the students' academic ability, and the teaching quality. The improvement of the lecturers' performance can be seen from their ability in designing, implementing, and evaluating the learning process. The improvement of the students' academic ability can be observed from the mastery of teaching materials, social skills, problem solving, self-confidence, and self-esteem. The improvement of teaching quality can be seen from the ability to attract the students' interest in attending the classes, enhance learning motivation, improve the learning interaction between the lecturers and the students, among the students, and with the other learning sources, and the impressive learning climate. The test results indicate that the scores of the experimental and control groups on each test improve, but the improvement of the test scores of the experimental group is significantly higher than the one of the control group. This indicates that the application of the cooperative learning model is more effective than the usual learning model. Another result indicates that the cooperative learning model that use changing learning teams is not significantly different from the one that uses fixed team. The practical implication of this study is that it can increase the willingness and ability of the lecturers, make the students learn, and improve the teaching quality. The theoritical implication is that it discovers the principles and theorems of cooperative learning for teaching social work methods.